Pengukuran dan Analisis Kebisingan Permukiman Tepi Rel Kereta Listrik - Erna Kusuma Wati (Universitas Indraprasta PGRI Jakarta, 2020)
Research on the distribution of noise level in settlement near the KRL (Electric Train) railway is conducted in Tebet Timur Dalam settlement, DKI Jakarta to determine if the Threshold Value (NAB) of noise in the settlement is by standards or not. If not, then a recommendation is needed to reduce the noise. The data are collected in two weeks, during which the grid method is used to determine the coordinates. Noise level data collection at each point is carried out within 24 hours of six time periods. The mapping of the distribution of noise is conducted using the Surfer application with kriging method, with data in the form of coordinates and measurement results. The coordinates are obtained using an android application called UTM Geo Map. The measurement results show the highest LSM noise level is at a distance of 20 meters in Gang C of 80.5 dBA, while the lowest LSM data result is at a distance of 80 meters from the noise source at Gang B of 54.2 dBA The recommended safe distance to establish a settlement is above 80 meters because it is according to the NAB. Another recommendation to reduce noise is to provide a barrier in the form of trees or concrete walls that limit the edge of the railway at a minimum distance as far as five meters from the residential area.